2009
DOI: 10.1557/jmr.2009.0108
|View full text |Cite
|
Sign up to set email alerts
|

Determination of plastic properties by instrumented spherical indentation: Expanding cavity model and similarity solution approach

Abstract: The present paper aims to develop a robust spherical indentation-based method to extract material plastic properties. For this purpose, a new consideration of piling-up effect is incorporated into the expanding cavity model; an extensive numerical study on the similarity solution has also been performed. As a consequence, two semi-theoretical relations between the indentation response and material plastic properties are derived, with which plastic properties of materials can be identified from a single instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…and a c can be determined by By considering the effect of piling-up on the volume displaced by hydrostatic core, a modified expanding cavity model (ECM) was developed in our previous study 23 to describe the relationship between indentation work and plastic properties as follows…”
Section: Methods Iv: Model Of Leementioning
confidence: 99%
See 2 more Smart Citations
“…and a c can be determined by By considering the effect of piling-up on the volume displaced by hydrostatic core, a modified expanding cavity model (ECM) was developed in our previous study 23 to describe the relationship between indentation work and plastic properties as follows…”
Section: Methods Iv: Model Of Leementioning
confidence: 99%
“…Recently, it has been shown that, with a spherical indenter, plastic properties can be determined from a single loading curve. 18,19,23 By reviewing the spherical indentation methods that have been developed, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] the five models selected for this study were those of Field and Swain, 14 Cao and Lu, 18 Zhao et al, 19 Lee, 11 and Jiang et al 23 Although there have certainly been many more studies performed on this topic, these five were selected for three reasons. First, they can be simply reproduced step by step according to only the procedures provided by the original literature; second, they offer a means of identifying the plastic properties solely by analyzing the load-depth data (that is, they do not rely on the physical measurement of residual impression); third, they are easy to implement experimentally (no difficulty is caused by repetitive loading and unloading, and only a small number of empirical parameters are used).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al [14,15] tried to reduce the pile up effect by measuring the residual indentation. Jiang et al [16] also introduced a correction factor related to the indentation value to take this pile up into account. However, it should be noted that these corrections are limited to a certain range of selected material properties.…”
Section: Indentation On Elastic-plastic Materialsmentioning
confidence: 99%
“…This method needs a large number of FEM computations within a certain range of the material properties defined as the power law equation. The dimensional function has established a relationship between the indentation characteristics and material properties [16,[73][74][75][76][77][78][79][80].  theorem is the key theorem in dimensional analysis, which could reduce complex physical problems to their simplest form [81,82].…”
Section: Determination Of Plastic Property Through Spherical Indentatmentioning
confidence: 99%